Situation Report: Czechoslovakia, 5 August 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Lessons from the History of Economic Reforms in Czechoslovakia / by Peter Martin A Prague Spring Economist's Comeback? / by Jan Obrman A Thematic Chronology of the August 1968 Invasion / by Vladimir Kusin Federal Assembly Delegation in the USA / by Adrian Pressburg How to Cope with the Increasingly Free Flow of Information / by Jan Obrman Charter 77 Appeals for Memorial to Victims of Stalinist Repression / by Adrian Pressburg A Complaint about Soviet Troops in Czechoslovakia / by Vladimir Kusin Czechoslovakia's Financial Malaise / by Peter Martin Czechoslovakia Cuts Growth Targets / by Vladimir Kusin